An Examination of Binanga High School Students' Literacy Capabilities - Hasibuan, Desy Rahmayanti (LAVOISIER: Chemistry Education Journal, 2023)
This study aims to analyze the literacy skills of high school students in Binanga. The research method used is descriptive research method with quantitative and qualitative approaches. The population in this study were high school students in class XI IPA in the odd semester of the 2021/2022 academic year in Barumun Tengah sub-district. A sample of 120 students was taken from 2 schools, namely class XI IPA SMAN 1 Barumun Tengah and class XI IPA MAN 2 Padang Lawas. The sampling technique used the cluster random sampling method. Data collection techniques with tests, questionnaires and the learning process. The results showed: 1) students' reading literacy skills were 52.02% very low category, 2) scientific literacy skills were 49.00% very low categories, 3) mathematical literacy skills were 50.26% very low categories.